Effect of a Combined Exercise and Dietary Intervention on Self-Control in Obese Adolescents - Xiang, Ming-Qiang; Liao, Jing-Wen; Huang, Jun-Hao; Deng, Hai-Lin; Wang, Dan; Xu, Zebo; Hu, Min (Frontiers in Psychology, 2019)
Objective: To determine whether a combined exercise and dietary intervention improved cognitive self-control and physical self-control and whether pre-to-post intervention changes in self-control were mediated by changes in body mass index (BMI) and maximal grip strength (MGS), in a sample of obese adolescents. Method: Forty-four obese adolescents were randomly assigned to a 6-week combined exercise and dietary program or a control group, and data from 36 participants (n=18 for each group) were analyzed. The combined exercise and dietary program was performed over 6 weeks, supervised by qualified trainers in a closed boot camp. The primary outcomes of this study were cognitive self-control and physical self-control, assessed by the Stroop task and a handgrip task, respectively. Secondary outcomes included BMI, MGS, trait self-control and physical activity level. Results: The combined exercise and dietary intervention improved both cognitive and physical self-control. Similar beneficial effects were also found for reduced BMI and enhanced MGS. The pre-to-post intervention changes in BMI and MGS significantly mediated improved physical self-control but not cognitive self-control. Conclusions: In obese adolescents, a combined exercise and dietary intervention is an effective approach to improving multiple aspects of self-control while reducing BMI and enhancing MGS. These findings also suggest that reduced BMI and enhanced MGS mediate specific aspects of self-control.